ANALISIS LOSSES KAPASITAS KETIDAKSEIMBANGAN DAYA BEBAN PADA TRANSFORMATOR DISTRIBUSI MENGGUNAKAN SIMULASI ETAP - Purnomo, Bayu; Gumilang, Fajar; Saleh, Haerul (Jurnal Teknik Elektro, 2025)
hen loading a transformer, it can be expected that the value of the loading will not exceed the set standard, namely 80%. When loading a transformer, it can also be expected that the loading values for each phase (R, S, and T) are balanced. However, if there is a load imbalance, it cannot exceed 25%. This results in the impact of the load imbalance resulting in a neutral conductor current and this neutral current will occur losses . The next stage is collecting data from the field related to the discussion that will be discussed. This data was obtained from one of the distribution transformers with a capacity of 2500 KVA belonging to PT. Shoe Manufacturing, the next stage is to calculate and simulate losses and load imbalance with neutral current using ETAP 12.6 software on the transformer. In the calculations and simulations it will later be used as a basic benchmark regarding load analysis on the transformer. Based on the calculations that have been carried out, a percentage of 4% can be obtained and the lowest is at night, namely 2 %. So that the load on the transformer can be balanced, load balancing can be done on each phase of the transformer. The peak load on the transformer occurs in the afternoon where the percentage is 30.9%. And the lowest occurred at night at 22.15%. However, power losses are greater in the afternoon compared to the evening, namely 85.35KW